Galdhöpiggen, London och Afrika: Namnbruk i läromedelstexter som förmedlar en världssyn (Namn och konflikter: Handlingar från NORNA:s 50:e symposium i Uppsala den 14–16 november 2023, 2025)
This study examines how place perceptions are presented through naming practices to young readers in school textbooks. The analysis focuses on the inclusion, presentation and contextualization of named places in Swedish textbooks from three subjects (mathematics, social sciences and Swedish language education), employing both quantitative and qualitative approaches. Furthermore, the study reveals shifts in place perceptions over time by comparing contemporary textbooks from the 2010s with historic textbooks from the 1920s. The findings indicate significant changes in geographical representation, reflecting broader societal shifts and highlighting the crucial importance of naming practices in the discursive construction of ideologically colored word views. While the 1920s textbooks display a primary focus on local, Nordic as well as rural places, constructing a strongly domestic and euro-centric worldview, by the 2010s, we find a more urbanized discourse with broader global representation. However, Europe remains prominent even in the contemporary textbooks and is contextually portrayed with a greater sense of closeness, familiarity and unity, contrasting with Asia and Africa, which are depicted as more foreign, tumultuous and non-attractive places. This study contributes to understanding the role of textbook naming practices in shaping students’ perceptions of the world and underlines the importance of critically examining authoritative educational materials for ideological biases.